Ekonomi Biru Kepulauan Riau Berkelanjutan: Tantangan, Peluang dan Langkah Strategik Berbasis Kolaborasi Pentahelix - Muhammad Alfarizi (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
Indonesia, as a global maritime axis nation, has a long history in sea trade that has shaped its cultural diversity. With its rich biodiversity and thousands of islands, Indonesia, particularly the Riau Islands, is a megabiodiverse country with strategic maritime potential. The national economy focuses on the concept of the